Synthesis and Antibacterial Activity of Some Substituted Azetidine-2-Ones - D. Prabhavat, Manoj; Vyawahare, A.R.; Ghiya, B.J. (Asian Journal of Chemistry, 2010)
The titled derivatives have been synthesized by condensing aryl and aryloxy acetyl chloride in presence of triethyl amine (TEA) with 1N-amino benzal-2-phenyl-4-arylidene-Δ2-imidazolin-5-ones, obtained by the reaction of 1N-amino-2-phenyl-4-arylidene-Δ2-imidazolin-5-ones with different aromatic aldehydes. The products have been characterised by IR, NMR and elemental analysis and have been screened for their antimicrobial activity.